An investigation of the role of the nucleus accumbens in the hippocampal learning-behaviour translation - Seaton, Adam (2019)
The hippocampus is required for important types of rapid everyday learning, including place learning. However, the pathways via which hippocampal place learning is translated into behaviour remain to be determined. The intermediate hippocampus is critical for the hippocampal learning-behaviour translation and combines neural substrates of accurate place encoding with links to prefrontal and subcortical behavioural control sites, which may contribute to this translation. The nucleus accumbens (NAc) is a main candidate due to strong hippocampo-NAc projections that have been implicated in behaviour based on place memory (Chapter 1).